The role of platelets in sepsis. Issue 1 (20th December 2020) - Shannon, Oonagh
Abstract: A State of the Art lecture titled "The role of platelets in sepsis" was presented at the ISTH congress in 2020. Sepsis is a life‐threatening organ dysfunction caused by a dysregulated and multifaceted host response to infection. Platelets play a significant role in the coordinated immune response to infection and therefore in the inflammation and coagulation dysfunction that contributes to organ damage in sepsis. Thrombocytopenia has a high incidence in sepsis, and it is a marker of poor prognosis. The genesis of thrombocytopenia is likely multifactorial, and unraveling the involved molecular mechanisms will allow development of biomarkers of platelet function in sepsis. Such platelet biomarkers can facilitate study of antiplatelet interventions as immunomodulatory treatment in sepsis. Finally, relevant new data on this topic presented during the 2020 ISTH virtual congress are reviewed.